2013
DOI: 10.2478/s11686-013-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in ectoparasite load in the Mehely’s horseshoe bat, Rhinolophus mehelyi (Chiroptera: Rhinolophidae) in a nursery colony in western Iran

Abstract: We studied variation of ectoparasite load in a free ranging populations of Mehely's horseshoe bat (Rhinolophus mehelyi) on five successive occasions in a nursery roost in western Iran. In total, 87 Rhinolophus mehelyi were captured. The patterns of abundance differed greatly among parasite species but total parasite load was markedly higher in pregnant females in spring and early summer and lower in solitary males. On average, 90% of bats were infested by Eyndhovenia sp. with a mean intensity of 13.79 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
3
1
2
Order By: Relevance
“…Scott and Kaufmann, 1991;Morales et al, 2002;Sharifi et al, 2013), although the opposite has been found in other studies (e.g. Osorio et al, 2008).…”
Section: Decrease Of Reproductive Performance Of Fleas On Pregnant Hostscontrasting
confidence: 49%
“…Scott and Kaufmann, 1991;Morales et al, 2002;Sharifi et al, 2013), although the opposite has been found in other studies (e.g. Osorio et al, 2008).…”
Section: Decrease Of Reproductive Performance Of Fleas On Pregnant Hostscontrasting
confidence: 49%
“…The bat fly was identified by external morphological features with a dissecting microscope and photomicroscope (MicroCap V3.0) using ( Theodor, 1957 , 1959 ) as identification guides. The ectoparasite abundance (number of ectoparasite per fruit bat), ectoparasite prevalence (percentage of infested fruit bat), and mean ectoparasite intensity (mean number of ectoparasite per infested bat) were determined ( Sharifi et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Spinturnix psi is a highly host-specific species, exhibiting marked morphological, physiological, and behavioral adaptations to M. schreibersii (Estrada-Peña et al, 1991;Lourenço & Palmeirim, 2007) and M. pallidus. Most studies on ectoparasites of bats in Iran are restricted to morphological (Malek-Hosseini & Zamani, 2017;Vatandoost et al, 2010) and ecological (Sharifi et al, 2008(Sharifi et al, , 2013 studies, and there is no specific and comprehensive study about the genetic association between the bats and their ectoparasites.…”
Section: Introductionmentioning
confidence: 99%